Study of the Factors Affecting the Selectivity of Catalytic Ethylene Oligomerization - Albahily, Khalid (Université d'Ottawa / University of Ottawa, 2011)
Over the past decade, advances in ethylene oligomerization have witnessed explosive growth of interest from both commercial and academic standpoint, with chromium metal invariably being the metal of preference. A common feature in this literature was the extended long debate regarding the mechanism, metal oxidation states responsible for selectivity and the role of the ligand. This thesis work embarked on the isolation and characterization of new active intermediates called “single component catalysts” (or self activating) to address two important questions: (1) how the catalyst precursors re-arrange upon activation and (2) the real oxidation state of the activated species. Four different ligands systems have been examined for this purpose. The first part is a study on the NPIIIN ligand which can be described as a dynamic and non-spectator ligand. Upon aluminum alkyl activation, a series of single component chromium catalysts for selective ethylene oligomerization and polymerization have been isolated, fully characterized and tested. New selective single component chromium(I) catalysts have also been isolated and tested positively for ethylene trimerization. The second part includes a new series of chromium complexes based on the NPVN ligand. This ligands enabled to obtain the first polymer-free extremely active catalytic system. In both NPN ligand systems, a new activation pathway was discovered by using vinyl Grignard reagent [(CH2=CH)MgCl] as activator and/or reducing agent. The third part explores new modified pyrrole-chromium complexes which were found to be highly active and selective ethylene trimerization catalysts. This part was a continuation of previous work from our lab to complete the mechanistic picture of this highly successful pyrrole-chromium catalyst independently commercialized by Phillips-Chevron and Mitsubishi. Interestingly upon aluminum alkyl treatment, the first example of a Schrock-type chromium ethylidene complex has been isolated and characterized and found to be a potent catalyst for selective ethylene trimerization. Finally, the other ligands introduced in this thesis are new systems called pyridine-SNS and Si-SNS that introduce some modification to the known commercial SNS catalyst (Sasol technology). The introduction of a pyridine ring or a silyl unit in the ligand scaffold has allowed to understand the mechanism of action of this remarkable system.
Keywords: Chromium; Ethylene Oligomerization; Trimerization; Alpha Olefins